Peran Storytelling dalam Promosi Wisata Budaya Kalimantan Tengah - I Made Puspe; Efraim Laluas; Andika Andika (Dharma Duta, 2026)
The development of the tourism industry in the digital age has driven changes in communication strategies for promoting tourist destinations, particularly cultural tourism. One communication approach that has emerged in modern tourism promotion is storytelling. Storytelling is not only used as a medium for conveying information but also as a communication strategy capable of fostering emotional engagement among tourists, strengthening cultural identity, and enhancing the image of tourist destinations. This study aims to analyze the role of storytelling in cultural tourism promotion, specifically within the context of Dayak culture in Central Kalimantan. The research employs a Literature Review method using a Systematic Literature Review (SLR) approach. Data were collected from various literature sources such as Google Scholar, Scopus, ScienceDirect, and Garuda, covering publications from 2015 to 2025. The findings indicate that storytelling plays a strategic role in cultural tourism communication as it fosters more authentic, emotional, and meaningful travel experiences. Digital storytelling via social media and digital platforms has also proven effective in expanding cultural tourism promotion to a global audience. Dayak culture holds significant potential as a source of cultural tourism narratives through its legends, traditional rituals, the Huma Betang philosophy, and the local wisdom values cherished by the Dayak community. However, the application of storytelling in cultural tourism promotion still faces various challenges, such as a shortage of creative human resources, a lack of documentation of local culture, and the risk of cultural commercialization. Therefore, an innovative, authentic, and sustainable digital communication strategy based on storytelling is needed to strengthen the cultural tourism identity of Central Kalimantan while supporting the preservation of local culture.